Determination of Employee Performance: Analysis of Employee Involvement, Job Satisfaction, Path Career and Remuneration - Liana, Esti; Indrawati, Nur Khusniyah (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The purpose of this literature review is to develop hypotheses for future researchers conducting research related to employee performance. The research article on employee performance determination: analysis of employee engagement, job satisfaction, career paths, and remuneration is a scientific literature article in the field of human resource management. The approach used in this literature review is descriptive qualitative. The data collection technique used is literature study or reviewing previous relevant articles. The data used in this study is secondary data, sourced from academic online media such as Thomson Reuters Journal, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. Empirical data is used to support the phenomena occurring in this study. In this study, previous research relevant to each topic was used, with one article reviewed for each topic. The results of the literature review are as follows: 1) Employee involvement influences employee performance; 2) Job satisfaction influences employee performance; 3) Career path influences employee performance; and 4) Remuneration influences employee performance.